The Role Of Sustainability Innovations And E- Bussiness, In Achieving Firm Performance With A Sustainable Competitive Advantage As Mediation - Dhyanasaridewi, I Gusti Ayu Diah; Augustine, Yvonne (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This research aims to analyze the roles of Sustainability Innovations and E-Business to achieve a superior Firm Performance with Sustainable Competitive Advantage as mediating variable. The data in this study were obtained through a survey, and thenan integrative research model was created to analyze the relationship using structural equation modeling with partial least squares (PLS).The empirical results indicate that sustainability innovation have a significant effect, either directly or indirectlythrough sustainable competitive advantage on company performance. Meanwhile, E-business only has a significant relationship with firm performance while mediating by a sustainable competitive advantage. Continuous innovation and shifting of company operations to E-business will affect the company’s activities and have the potential to create competitive advantages among its competitors, which in turn will affect in achieving better performance. This research implication is to make the management as a policymaker in the organization aware of the urgency to create a sustainability innovation and switch to e-business, to be in a position to compete and also achieve a better firmperformance.